Base editing strategy for insertion of the A673T mutation in the APP gene to prevent the development of AD in vitro - Antoine Guyon; Joël Rousseau; Francis-Gabriel Bégin; Tom Bertin; Gabriel Lamothe; Jacques P. Tremblay (Elsevier, 2021)
The amyloid precursor protein (APP) is a transmembrane protein mostly found in neurons. Cleavage of this protein by β-secretase can lead to the formation of amyloid-β (Aβ) peptide plaque, which leads to Alzheimer's disease. Genomic analysis of an Icelandic population that did not show symptoms of Alzheimer's at an advanced age led to the discovery of the A673T mutation. This mutation can reduce β-secretase cleavage by 40%. We hypothesized that the insertion of this mutation in patients' neurons could be an effective and sustainable method of slowing down or even stopping the progression of Alzheimer's disease. We modified the APP gene in HEK293T cells and in SH-SY5Y neuroblastoma using a Cas9 nickase (Cas9n)-deaminase enzyme to convert the alanine codon to a threonine. Several Cas9n-deaminase variants were tested to compare their efficiency of conversion. The results were characterized and quantified by deep sequencing. We successfully introduced the A673T mutation in 53% of HEK293T cells alongside a new mutation (E674K), which seemed to further reduce Aβ peptide accumulation. Our approach aimed to provide a new strategy for the treatment of Alzheimer's and in so doing, demonstrate the capacity of base editing techniques for treating genetic diseases.